Dating of Sediments by physics methods Electron Paramagnetic Resonance (EPR) in the region of Iguape – Cananéia, Brazil. (Brazilian Journal of Radiation Sciences, 2021)
Dating of sediments was used by physics method in this work, in the physics methods the radioactivity is present, but usually it is method based on the storage of energy of radiation in the solid, in which will be employed. In the present work, Icapara sediment dating was used Electron Paramagnetic Resonance (EPR) method, in this technique the energy absorption occurs when the frequency of the incident wave is in resonance with the energy difference made by the magnetic field between the parallel and antiparallel directions to this field with the irradiated sample that creates defects in its structure.  In the state of S˜ao Paulo, in the region of Iguape on the southeast coast, it is a place called Icapara, a large sand terrace that was formed due to sea level fluctation that ocorred more than 130 thousand years ago. A sample was taken from a point about 9 meters above the current control of the sea. An age of about 38,000 ±12,000 and 46,000 ± 7,000 years were obtained (EPR) to correlate with the Quaternary period and will be presented to the data obtained.